Effects of Di-Isononyl Phthalate (DiNP) on Follicular Atresia in Zebrafish Ovary - Godoi, Filipe G. Andrade; Forner-Piquer, Isabel; Randazzo, Basilio; Habibi, Hamid R.; Lo Nostro, Fabiana L.; Moreira, Renata Guimarães; Carnevali, Oliana (Frontiers in Endocrinology, 2021)
Di-isononyl phthalate (DiNP) is a plasticizer reported to elicit hormone-like activity and disrupt metabolism and reproduction in fish and other vertebrates. In general, phthalates have been used at high concentrations beyond reported environmental levels to assess their adverse effects on fish gonadal physiology. The present study exposed adult female zebrafish to a wide range of DiNP concentrations [0.42 µg L-1 (10-9 M), 4.2 µg L-1 (10-8 M), and 42 µg L-1 (10-7 M)] for 21 days. We evaluated gene expression profiles related to apoptosis, autophagy, and oxidative stress; DNA fragmentation (TUNEL assay: Terminal deoxynucleotidyl transferase dUTP nick end labeling) and Caspase activity (CAS3) were also examined. Exposure to 0.42 and 4.2 µg L-1 upregulated the genes coding for tnfa and baxa, sod1, prkaa1, respectively. CAS3 immunohistochemistry revealed a higher number of positive vitellogenic oocytes in ovaries exposed to 0.42 µg L-1. Subsequently, we examined the relationship between CAS3 signaling and DNA fragmentation. Accordingly, DNA fragmentation was observed in vitellogenic follicles of fish exposed to 0.42 and 4.2 μg L-1. Our results demonstrate that follicular atresia can occur after exposure to environmental levels of DiNP for 21 days, which may adversely affect the reproductive performance of female zebrafish in a non-monotonic manner.